Analisis dan Rekonstruksi LKPD Praktikum Osmosis Menggunakan Diagram Vee - Adika Muhammad Aziz; Bambang Supriatno; Amprasto Amprasto (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2025)
Practical activities are a learning method that can involve students in constructing their own understanding. A good practicum activity must be guided by a structured instruction sheet or student worksheet that is able to lead students to understanding. The purpose of this research is to produce a worksheet for students of osmosis practicum that is reconstructed using Vee diagrams. The method used in this research is descriptive qualitative method. The results of this study indicate that the LKPD of osmosis practicum that has been analyzed has deficiencies in the purpose or focus of the question made, besides that there are still deficiencies in procedures and data transformation so that it does not lead to the desired conclusion. Reconstruction was carried out using Vee diagrams so that the resulting LKPD for osmosis practicum had all the criteria for the Vee diagram assessment score. Based on the results of the scores obtained on the reconstructed osmosis practicum LKPD, it shows that the LKPD is feasible and can be used in guiding students in osmosis practicum activities. From the results of the reconstruction carried out, it is hoped that the reconstructed products using Vee diagrams can guide students in constructing their own understanding. In addition, in the future, the reconstruction of LKPD using Vee diagrams can be further developed.